A comparison of undergraduate teaching of psychiatry across medical schools in the Republic of Ireland. (8th June 2020) - Byrne, F.; Murphy, R.; O'Rourke, L.; Cotter, D.; Murphy, K. C.; Guerandel, A.; Meagher, D.; Sweeney, E.; Gill, M.; Campbell, A.; McDonald, C.; Hallahan, B.
Abstract : Objectives: To examine the delivery and assessment of psychiatry at undergraduate level in the six medical schools in the Republic of Ireland offering a medical degree programme. Methods: A narrative description of the delivery and assessment of psychiatry at undergraduate level by collaborative senior faculty members from all six universities in Ireland. Results: Psychiatry is integrated to varying degrees across all medical schools. Clinical experience in general adult psychiatry and sub-specialities is provided by each medical school; however, the duration of clinical attachment varies, and the provision of some sub-specialities (i.e. forensic psychiatry) is dependent on locally available resources. Five medical schools provide 'live' large group teaching sessions (lectures), and all medical schools provide an array of small group teaching sessions. Continuous assessment encompasses 10–35% of the total assessment marks, depending on the medical school. Only one medical school does not provide a clinical examination in the form of an Objective Structured Clinical Examination with viva examinations occurring at three medical schools. Conclusions: Many similarities exist in relation to the delivery of psychiatry at undergraduate level in Ireland. Significant variability exists in relation to assessment with differences in continuous assessment, written and clinical exams and the use of vivas noted. The use of e-learning platforms has increased significantly in recent years, with their role envisaged to include cross-disciplinary teaching sessions and analysis of examinations and individual components within examinations which will help refine future examinations and enable greater sharing of resources between medical schools.